DAMPAK PENGEMBANGAN SHALE OIL AMERIKA SERIKAT TERHADAP OPEC (ORGANIZATION of EXPORTING COUNTRIES) - Lestari, Bunga Ayu; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research discusses about the implication of shale oil development to OPEC revenues. United States is one of the biggest energy consumption states. As a superpower state that becomes the second biggest country in energy consumption, United States has to keep its energy security resilence. Therefore, United States begins to develop alternative energy, such as shale oil resources. Shale oil development reach the successes which has been consumed for a half of total energy consumption in the United States lately. United States has a lot of shale oil resources in the country that do not only decrease the oil prices but also become a substitution of energy in US. The substitution does implication to OPEC revenues. This research using a level analysis of state, the used perspective is structuralism perspective to understand the implication of shale oil development. This research is based on library research which takes data from book, relevant, journal, newspaper and internet. In this research, the writer uses qualitative research method. OPEC is the biggest oil exporting.Keyword: Energy, Shale Oil, Impact, Energy Subtitution, Oil, Opec, Ex